ANALISIS KESESUAIAN PERAIRAN UNTUK WISATA SNORKELING DAN DIVING DI PULAU PISANG BAGIAN UTARA KECAMATAN PESISIR UTARA LAMPUNG BARAT - Lazuardi, Irfan; Subardjo, Petrus; Hariyadi, Hariyadi (Departemen Ilmu Kelautan, Fakultas PerikanJurusan Ilmu Kelautan, Universitas Diponegoro)
Pisang Island is one of the islands located in the Coastal West Lampung regency precisely in West Lampung. Expected with the development of Pisang Island as a tourist destination it will beable to increase revenue and the welfare of society in western Lampung. Utilization of coastal and marine resources in West Lampung could be the development of nautical tourism in the region in this regard Pisang Island. One form of nautical tourism is snorkeling and diving activities. However, in the tourist development efforts in Pisang Island have held identification and approach problems first. The most fundamental and the purpose of this studyis to conducta study on the suitability of water level in Pisang Island, especially for snorkeling and diving tourism activities. Research carried out by field observations (collecting primary data and secondary data) for 2 months in July 2011 to August 2011 in the northern part of the Pisang Island, which is divided into thirteen point sampling locations. Primary data collection consisted of coral cover data retrieval and type of life formusing LIT, count the number off is husing visual census of fish and measure the brightness levels use these cchidisk. The method used for the analysis of the research is descriptive method of analysis with the help of Travel Suitability Index which produces the suitability andvalue of the carrying capacity of tourist areas. Based on the results obtained from the calculation of travel suitability index for snorkeling and diving touris snorkeling tours there instations 1, 2, 3, and 5 are located at a depth of 3 meters. And for diving there instations 6, 7, 8, 9, 11, 12, 13 and 14 are located at a depth of 5 meter still 10 meters.